Modulation and coding scheme selection in multimedia broadcast over a single frequency network-enabled long-term evolution networks - Alexiou, Antonios; Bouras, Christos; Kokkinos, Vasileios; Papazois, Andreas; Tsichritzis, George (International journal of communication systems, 2012)
SUMMARY Long term evolution constitutes the next generation cellular network beyond 3G that is designed to support the explosion in demand for bandwidth‐hungry multimedia services in wireless networks by providing an extremely high performance radio access technology. To support multimedia broadcast/multicast services (MBMS), long term evolution offers the functionality to transmit MBMS over a single frequency network, where a time‐synchronized common waveform is transmitted from multiple cells for a given duration. This enables over‐the‐air combining, thus significantly improving the spectral efficiency (SE) compared with conventional MBMS operations. In MBMS over a single frequency network transmissions, the achieved SE is mainly determined by the modulation and coding scheme selected. This study proposes and evaluates four approaches for the selection of the modulation and coding scheme. Each approach corresponds to different users' distribution and multimedia traffic conditions. On the basis of SE measurements, we determine the approach that either maximizes or achieves a target SE for the corresponding users' distribution and traffic conditions. Copyright © 2011 John Wiley & Sons, Ltd. This study proposes and evaluates four approaches for the selection of the modulation and coding scheme during multimedia broadcasting in long term evolution systems. Each approach corresponds to different users' distribution and multimedia traffic conditions. The spectral efficiency measurements performed through simulation experiments determines the approach that either maximizes or achieves a target spectral efficiency for the corresponding users' distribution and traffic conditions.